Evaluation of Corporate Social Responsibility Practices: A Descriptive Analysis of the Agricultural Sector in the Municipality of Ahome - López Alvarez, Alejandro; Lopez-Nevarez, Virginia; Solano-Noriega, Jesus Jaime; Zavala-Nevarez, Manuel Alejandro (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
Agricultural enterprises are pivotal to the municipality of Ahome, exerting substantial influence across economic, societal, and environmental dimensions. This study endeavors to examine and evaluate the corporate social responsibility (CSR) practices of these entities through the lens of the ISO 26000 framework and Good Agricultural Practices (GAP). The analysis encompasses the seven core subjects delineated by ISO 26000 and the principles of GAP, revealing performance levels ranging from regular to exemplary, contingent upon the inherent nature of each criterion. Remarkably, regulatory-driven criteria exhibit superior outcomes, whereas voluntary initiatives tend to underperform.